Pengaruh Kepemilikan Institusional, Komisaris Independen Dan Komite Audit Terhadap Integritas Informasi Laporan Keuangan - Efrianti, Desi (Jurnal Ilmiah Ranggagading (JIR), 2012)
The objective of this study is to analyze Integration of Financial Statements Information by investigating Conservatism Score Index by use of the approach documented by Mayangsari (2003) and Penmann and Zhang (2002) . In this study, it is investigated whether Ownership Institutional Proportion, independence commisioner, and audit commitee affects to the Integration of Financial Statements Information. This results of this study us of the approach signaling theory and agency theory. Multivariate Regretion analysis is used moderating to examine Hypothesis. The results of this study takes sample from 135 companies (firm years) in the manufacturing, Industrial at the Indonesian Stock Exchange and Indonesian Capital Market Directory years of 2006, 2007, 2008, 2009, and 2010, which were published in financial report from 2006- 2010. However, the final sampling indicates that just 98 (firm years) data samples were provided. The reduction of final data samples due to there are 10 data samples was delisted from BEI, 18 uncomplete financial statements and closing books date is 31 Desember, 9 data samples did not use Rupiah currency. The method of analysis taken as a sample of this research using purposive sampling. Documented is empirical evidence Ownership Institutional Proportion, independence commisioner, and audit committee significantly related to the Integration of Financial Statements Information. The result indicated that Ownership Institutional Proportion, independence commisioner, and audit commitee is significantly affected to the Integration Information of Financial Statements Information.